Insect Herbivores of Coccoloba cereifera Do Not Select Asymmetric Plants - Telhado, Cristina; Esteves, Daniela; Cornelissen, Tatiana; Fernandes, G. Wilson; Carneiro, Marco Antonio A (Environmental entomology, 2010)
Fluctuating asymmetry (FA) represents small, random variations from the symmetric bilateral pattern, and it is a frequently used measurement of plant and animal stresses. Some studies have shown a relationship between FA and herbivory, suggesting that FA might be a reliable indicator of plant quality and plant susceptibility to herbivore attack. In this study, we investigated the relationship between leaf FA of Coccoloba cereifera Schwacke (Polygonaceae) and the pattern of attack by the scale insect Abgrallaspis cyanophylly Signoret (Hemiptera: Diaspididae). Thirty individuals of C. cereifera were marked and followed during 2007 in southeastern Brazil, and all leaves of three shoots per plant were sampled, numbered, and categorized as young, mature, or senescent. We measured right and left widths of all leaves after digitizing the images to determine levels of FA for each leaf sampled per plant. Individuals of A. cyanophylli were counted using a stereoscope in the laboratory to determine infestation levels. Leaves of C. cereifera exhibited true patterns of FA, as shown by the normal distribution of asymmetry values. We observed high variation in attack rates by A. cyanophylly among C. cereifera individuals, with 43.3% of plants with no insects, whereas others exhibited up to 23,000 insects. No statistically significant relationship was observed between variation in FA and variation in A. cyanophylli among plants. These results suggest that FA cannot be used as an indicator of plant quality and susceptibility to herbivore attack but suggest that herbivores themselves might act as plant stressors.